2020
DOI: 10.1186/s12864-019-6256-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics applied to Mucor species with different lifestyles

Abstract: Background: Despite a growing number of investigations on early diverging fungi, the corresponding lineages have not been as extensively characterized as Ascomycota or Basidiomycota ones. The Mucor genus, pertaining to one of these lineages is not an exception. To this date, a restricted number of Mucor annotated genomes is publicly available and mainly correspond to the reference species, Mucor circinelloides, and to medically relevant species. However, the Mucor genus is composed of a large number of ubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 116 publications
(156 reference statements)
1
21
1
Order By: Relevance
“…Mucor genomes harbor also numerous Helitrons, known for their rolling circle replication mechanism. The presence of Helitrons has been observed in other Mucor species previously ( Lebreton et al, 2020 ). Noteworthy, Helitrons often hijack neighboring genes and are efficient vectors of HGT in other fungi ( Castanera et al, 2014 ).…”
Section: Resultssupporting
confidence: 69%
“…Mucor genomes harbor also numerous Helitrons, known for their rolling circle replication mechanism. The presence of Helitrons has been observed in other Mucor species previously ( Lebreton et al, 2020 ). Noteworthy, Helitrons often hijack neighboring genes and are efficient vectors of HGT in other fungi ( Castanera et al, 2014 ).…”
Section: Resultssupporting
confidence: 69%
“…Sequencing of five different Mucor genomes from strains that represented different environments and lifestyles identified homologs of genes involved in different mechanisms of iron acquisition. Similar to R. delemar, the results suggested that Mucor species relied predominantly on Rhizoferrin for iron acquisition (Lebreton et al, 2020). However, the two strains associated with cheese production showed a reduced number of genes related to iron acquisition.…”
Section: Iron and Acquisitionmentioning
confidence: 81%
“…The genomes of Apophysomyces species show a unique profile of carbohydrate active enzymes (CAZymes) responsible for the generation of Apophysomyces cell wall polysaccharides, which may represent a novel antifungal target (Prakash et al, 2017). Difference patterns in CAZymes repertoire was also observed in the genomes of Mucor species that differed in lifestyle (Lebreton et al, 2020). Notably, Mucor species involved in cheese ripening had less CAZymes in their genome compared to more pathogenic and clinical isolates.…”
Section: Mucorales Growth and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucor genomes harbour also numerous Helitrons, known for their rolling circle replication mechanism. The presence of Helitrons has been observed in other Mucor species previously [41]. Noteworthy,…”
Section: Repetitive Elementsmentioning
confidence: 61%